Research Progress and Analysis on Toxicity of Microplastics to Marine Medaka (Oryzias melastigma) - Jian MA; Youxun LI; Daode YU; Zhonghua ZHAO; Jingyun TIAN; Xungang TAN; Shuguo LYU; Xianlei WANG (Haiyang Kaifa yu guanli, 2023)
This study focused on the research progress of the toxicity of microplastics to marine medaka. By consulting the relevant literatures, the annual change and regional distribution of the published papers were statistically analyzed. In addition, the type, size and concentration of microplastics, exposure time and mode, and selection of marine medaka were studied. Besides, this paper summarizes six aspects of the research results: metabolism in vivo, intestinal injury, growth and developmental toxicity, reproductive toxicity, genetic toxicity and amplification or mitigation effect to other marine pollutants. In the end, it is suggested that experimental time, selection of microplastics and toxicological mechanism need to be considered in future study.